In-Cell Western Assays to Evaluate Hantaan Virus Replication as a Novel Approach to Screen Antiviral Molecules and Detect Neutralizing Antibody Titers - Ma, Hong-Wei; Ye, Wei; Chen, He-Song; Nie, Tie-Jian; Cheng, Lin-Feng; Zhang, Liang; Han, Pei-Jun; Wu, Xing-An; Xu, Zhi-Kai; Lei, Ying-Feng; Zhang, Fang-Lin (Frontiers in Cellular and Infection Microbiology, 2017)
Hantaviruses encompass rodent-borne zoonotic pathogens that cause severe hemorrhagic fever disease with high mortality rates in humans. Detection of infectious virus titer lays a solid foundation for virology and immunology researches. Canonical methods to assess viral titers rely on visible cytopathic effects (CPE), but Hantaan virus (HTNV, the prototype hantavirus) maintains a relatively sluggish life cycle and does not produce CPE in cell culture. Here, an in-cell Western (ICW) assay was utilized to rapidly measure the expression of viral proteins in infected cells and to establish a novel approach to detect viral titers. Compared with classical approaches, the ICW assay is accurate and time- and cost-effective. Furthermore, the ICW assay provided a high-throughput platform to screen and identify antiviral molecules. Potential antiviral roles of several DExD/H box helicase family members were investigated using the ICW assay, and the results indicated that DDX21 and DDX60 reinforced IFN responses and exerted anti-hantaviral effects, whereas DDX50 probably promoted HTNV replication. Additionally, the ICW assay was also applied to assess NAb titers in patients and vaccine recipients. Patients with prompt production of NAbs tended to have favorable disease outcomes. Modest NAb titers were found in vaccinees, indicating that current vaccines still require improvements as they cannot prime host humoral immunity with high efficiency. Taken together, our results indicate that the use of the ICW assay to evaluate non-CPE Hantaan virus titer demonstrates a significant improvement over current infectivity approaches and a novel technique to screen antiviral molecules and detect NAb efficacies.